Pengaruh Pengetahuan Perpajakan Terhadap Pemilihan Karir Sebagai Konsultan Pajak Dengan Peluang Kerja Sebagai Moderasi - Atikah Nur 'Aini (Yayasan Literasi Ilmiah Indonesia, 2024)
Purpose: The main objective of this study is to determine how the tax profession influences career choice as a tax consultant and also to consider the influence of job opportunities as a moderating factor. Method: This study involved Accounting students from various universities in Indonesia, the snowball sampling method was used to collect data from 371 respondents in 54 universities in Indonesia. IBM SPSS Statistics 25 was used to perform linear regression analysis for data processing and Microsoft Excel was used for data tabulation. Finding: The findings show that tax knowledge significantly influences career choice as a tax consultant. This study reveals that job opportunities can significantly moderate the relationship between tax knowledge and career choice as a tax consultant. Novelty: This research is motivated by the phenomenon of the low tax knowledge of accounting students towards choosing a career as a tax consultant. So this research is interesting to study and re-test the differences in the results of previous studies. The novelty of this research is that previous researchers used independent and dependent variables while in this study the author added job opportunities as a moderating variable.